A high-throughput RNA sequency of peripheral blood mononuclear cells reveals on inflammatory state in women with PCOS - Heidarzadehpilehrood, Roozbeh; Pirhoushiaran, Maryam; Osman, Malina Binti; Ling, King-Hwa; Abdul Hamid, Habibah (Elsevier Inc., 2025)
Background: Polycystic ovary syndrome (PCOS) is an endocrine and reproductive condition affecting women of reproductive age, although its expression profiles and molecular pathways are not fully understood. Aims: To identify the transcriptome expression profiles of peripheral blood mononuclear cells (PBMCs) in women with PCOS and controls. To investigate noninvasive diagnostic biomarkers and potential treatment targets to improve women's fertility. Methods: RNA sequencing (RNA-Seq) was conducted on PBMC samples from six patients with PCOS and six healthy controls. qRT-PCR validation was carried out in 68 subjects. Multivariate logistic regression was performed to assess the combined impact of biomarkers. Results: A total of 186 differentially expressed genes (DEG) were found between patients and controls (log2FC >1, p < 0.05). Enrichment analysis revealed cytokine-mediated signaling pathways, cytokine activity, and cytokine-cytokine receptor interaction. RNA sequencing showed consistency with qRT-PCR. Women with PCOS had significantly higher levels of AQP9 (p < 0.001), PROK2 (p = 0.001), and S100A12 (p < 0.001) expression compared to controls. AQP9 (AUC = 0.77), PROK2 (AUC = 0.71), and S100A12 (AUC = 0.82) adequately discriminated women with PCOS from healthy controls. In addition, multiple logistic regression on biomarkers resulted in a significant diagnostic power with an AUC = 0.89, 95 % CI: 0.81–0.97, p < 0.0001. Further associations were analyzed between relative gene expression and clinical, anthropometric, hormonal, and ultrasonographic data. Conclusions: Dysregulated RNA expression in PBMCs may contribute to an increased risk of PCOS and serve as a potential diagnostic biomarker. The involvement of inflammatory and cytokine-related pathways supports the notion that PCOS is a chronic inflammatory condition.